G49(P) Reversal of carotid intima-media thickness with lipid lowering therapy in children with familial hypercholesterolaemia-case reports of two patients. (12th March 2018) - Sri, A; Alexander, S; KAzmi, F; Stracey, H; Feher, M
Abstract : Background: Children with heterozygous familial hypercholesterolaemia (FH) are known to have early asymptomatic morphological changes of the vessel wall. Measurement of the carotid intima-media thickness (CIMT) is a useful marker of endothelial function and effectiveness of lipid-lowering therapy. Reversibility of CIMT with statin therapy have been reported in adults. However, in children, only one RCT reports regression of CIMT with statins. We report two children with FH demonstrating a significant CIMT reduction following therapy. Case1: A 16 year old male was diagnosed at 9 years with an extensive maternal history and a total cholesterol (TC) of 8.8 mmol/L, LDL-C 7.09 mmol/L. CIMT at diagnosis was normal at 0.3 mm bilaterally. Rosuvastatin was commenced at 10 years of age. Serial CIMT measurements over 4 years showed an increase to 0.7 mm prompting addition of Ezetimibe and an increase of Rouvastatin to 20 mg daily. Subsequently, CIMT reduced to 0.4–0.5 mm bilaterally after 13 months. CIMT measurements have remained stable since. The latest profile – TC is 3.7 mmol/L, LDL-C 2.32 mmol/L. Case 2: A 19 year old male, with a maternal history of FH, was diagnosed at 12 years of age with a TC 8.5 mmol/L and LDL-C 6.4 mmol/L. CIMT was increased at 1.0 mm bilaterally at diagnosis. He was treated with Rosuvastatin (maintenance dose 20 daily). Serial CIMTs were initially stable with no progression. Subsequently, 60 months after commencing statins, there was an improvement to 0.4 mm on both sides which has since remained stable. The latest profile- TC is 4.3 mmol/L, LDL-C 2.94 mmol/L. No plaque disease was seen in either patients. CIMT was measured at common carotid arteries. Discussion: CIMT is a useful non-invasive method to help clinical decision making in children with FH. Serial measurements in our patients have shown that an abnormal CIMT is reversible in children following lipid lowering therapy. Further trials with CIMT as an outcome measure may be useful to determine the ideal age to commence statin treatment in children.